Kewenangan Dan Tanggung Jawab Pemerintah Daerah Terhadap Penyediaan Prasarana Jalan - Br Gurusinga, Ena Bina; Matitaputty, Merlien Irene (Jurnal Saniri, 2023)
There is authority and responsibility of the goverment in provinding road infrastructure to ensure the fulfillment of road infrastructure as stipulated in article 5 of law number 22 of 2009. The issue being discussed is whether the goverment is responsible if road infrastructure is not availaibleProvide input academically in the development of constitutional law related to the government’s responsibility for the provision of road infrastructure in law number 22 of 2009.This research is a normative legal research, statute approach, conceptual approach, primary legal materials, and secondary legal materials. Primary legal materials are linked to secondary legal materials where the management and analysis of legal materials is carried out qualitatively. Research shows that there is government responsibility and authority for the provision of road infrastructure for the common interest in order to create prosperity.